The detrimental impact of smoking on osteoporosis: A narrative review - Fatima Amer Hassan; Falah Hassan Shari; Ausama Ayob Jaccob (Zagazig Journal of Pharmaceutical Sciences, 2025)
Background: Passive smoking causes an annual death rate, making tobacco use a serious health concern. Chronic smoking is a social risk factor for bone illnesses such as osteo-malacia, diabetic osteopathy, and Paget's disease because it deteriorates muscle function and bone density. The predominant causes for these disorders are a deficiency of osteoblasts in producing bone cells or an increased rate of bone resorption by osteoclasts. Nonetheless, the precise chemicals in cigarette smoke that induce these alterations remain unidentified. Researchers have examined the mechanism of bone turnover in metabolic bone diseases using bone turnover biomarkers and bone density ratio. Research indicates that cigarette smoke alters fracture hematoma development, impedes the healing process and influences the action of cytokines and growth factors at the fracture location. Conclusion: Quitting smoking is essential for decreasing the prevalence of skeletal problems and assessing smokers' potential for osteoporosis and fractures. Additional study is required to assess smokers' risk and design an approved pharmacological treatment.